The Impact of Social Media on Language Learning and Use - Ismatov, Sarvar (The Lingua Spectrum, 2025)
Social media play an important role in language learning and use, influencing both the formation of new language practices and the development of communication skills. Through platforms such as Twitter, Instagram, TikTok and others, users actively use simplified language, abbreviations, emojis and memes, which contributes to the formation of new language forms. At the same time, social media helps people from all over the world exchange knowledge and practice foreign languages, providing unique opportunities for language practice in an informal setting. They create a space for more flexible and free communication, where language experiments are often allowed. However, the negative impact is manifested in a decrease in literacy levels, especially among young people accustomed to quick messaging and the absence of formal norms. In general, social media influences language both positively and negatively, opening up new horizons, but also creating challenges for the traditional approach to language teaching. The author explores how social media can serve as a medium for language practice, facilitating communication and immersion in the language, and how they can contribute to the emergence and spread of informal forms of language, abbreviations and slang.